Замените уравнение равносильным ему квадратным уравнением: 1) -5x(x+6)=4(x-3)-10 2) (х-3)(3х+9)=(х--8)(х+9) 3) (х-8)(2х+3)=(3х=5)(х+4) 4) (у-7)(7у+49)=(у+8)(у-7)

Sweetkristina Sweetkristina    2   26.05.2019 23:10    0

Ответы
msimaratp08h7f msimaratp08h7f  23.06.2020 15:51

1) -5x(x + 6) = 4(x - 3) - 10,

   -5х² - 30х =4х - 12 - 10,

   -5х² - 30х = 4х - 22,

   -5х² - 30х - 4х + 22 = 0,

   -5х² - 34х + 22 = 0,

   5х² + 34х - 22 = 0;

2) (х - 3)(3х + 9) = (х - 8)(х + 9),

    3х²+ 9х - 9х - 27 = х² + 9х - 8х - 72,

    3х²- 27 = х² + х - 72,

    3х² - 27 - х² - х + 72 = 0,

    2х² - х + 45 = 0;

3) (х - 8)(2х + 3) = (3х - 5)(х + 4),

    2х² + 3х - 16х - 24 = 3х² + 12х - 5х - 20,

   2х² - 13х - 24 = 3х² + 7х - 20,

    2х² - 13х - 24 - 3х² - 7х + 20 = 0,

    -х² - 20х - 4 = 0,

    х² + 20х +4 =0;

4) (у - 7)(7у + 49) = (у + 8)(у - 7),

    7у² + 49у - 49у - 343 =у² - 7у + 8у - 56,

    7у²- 343 = у² + у - 56,

    7у² - 343 - у² - у + 56 = 0,

    6у² - у - 287 = 0.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика